Uniaxial compressive properties of human lumbar 1 vertebrae loaded beyond compaction and their relationship to cortical and cancellous microstructure, size and density properties - Yeni, Yener N.; Dix, Michael R.; Xiao, Angela; Oravec, Daniel J. (Journal of the mechanical behavior of biomedical materials, 2022)
Lumbar 1 vertebrae are among those most commonly fracture due to osteoporosis. The strength of human vertebrae and its structural, microstructural and material determinants have been the subject of numerous studies. However, a comprehensive evaluation of properties beyond maximum load to fracture has not been available for the L1 vertebrae. The objective of this study was to document these properties in association with each other and with the geometric, density and cancellous and cortical structure properties for human L1 vertebrae. Bone volume fraction (BV/TV), trabecular thickness (Tb.Th), trabecular number (Tb.N), trabecular separation (Tb.Sp), connectivity density (Conn.Dn), degree of anisotropy (DA), structure model index (SMI) and fractal dimension (FD) of the cancellous microstructure, tissue mineral density (TMD), and thickness of the cortical shell (Sh.Th) and superior and inferior endplates thicknesses (EP.Th.S and EP.Th.I) were measured using microcomputed tomography for 27 cadaveric L1 vertebrae. Volumetric cancellous, shell and integral bone mineral densities (vBMD, shBMD and iBMD) as well as vertebral volume (V), height and width were measured using high resolution CT. Areal whole vertebral body and regional BMDs were measured using dual energy x-ray absorptiometry (DXA) in coronal and lateral views. Specimens were then uniaxially compressed to 15% of their height to obtain vertebral stiffness (K) and strength (Fmax) as well as displacement (D), force (F) and energy (W) properties at characteristic points of the load-displacement curve including yield (y), fracture (f), compaction (c), final displacement (t) and residual after unload (r). Correlation and principal component analyses suggested displacements to failure (Df), collapse (Dc) and recovery (Dr) contain information distinct from strength and stiffness. Bone size (V) was present, independently, in multiple regression models of K, Fy, Wy, Fmax, Df, Wt, Wfc and Dr (p < 0.05 to p < 0.0001), areal BMD in models of Dy, Wy, Fmax, Wf, Fc, Wt, Wyf and Wct (p < 0.04 to p < 0.0001), Sh.Th in models of Df, Fc and εr (p < 0.02 to p < 0.002), EP.Th.S in models of Fc and Wct (p < 0.004 to p < 0.0006), EP.Th.I in the model of Wct (p < 0.02), FD in models of Fy, Dy and Fmax (p < 0.03 to p < 0.004), Tb.Sp in models of K and Dy (p < 0.002 to p < 0.0004), Conn.Dn in the model of Df (p < 0.0009), and SMI in the model of Wt (p < 0.02). R2adj varied from 0.12 (Dr) to 0.80 (Wt) for the multiple regression models for all significant variables. In conclusion, there is distinct information in forces and displacements associated with characteristic events occurring during uniaxial compression and recovery, specifically in displacements associated with compaction and recovery. Though there are common factors such as bone mass for some, distinct cancellous and cortical features likely contribute to these events in L1. The descriptive data reported here are expected to provide reference values for comparative and model building efforts, and the relationships found are expected to provide insight into mechanical functions of an L1 vertebra. •Lumbar 1 is a common site of osteoporotic vertebral fracture.•We characterized the entire uniaxial compression behavior of human L1 vertebrae.•Compaction and recovery properties are distinct from those at yield and fracture.•Bone density is not a determinant of all structural mechanical properties.•Different microstructures contribute to force, displacement and work variables.